Estudio de un magnetrón utilizando el método de elementos finitos - Pérez Caro, Erik Alfredo (Pontificia Universidad Católica del Perú, 2021)
Magnetron sputtering system is a technique that consists in extracting atoms from a target material by collisions of energetic ions of an inert gas. It is widely used in semiconductor industries and materials processing research for developing thin films by deposition. During this process a low temperature capacitively coupled plasma is generated near the cathode and several variations of the properties of this plasma can affect the thin film deposition process and quality. An approach to study these types of systems is by computational modeling. The use of robust computational codes that can handle complicated geometries and can solve complex systems of differential equations. In this present project we aim to model numerically a system of magnetrons developed at the Materials Science and Renewable Energies (MatER) laboratory. Using the geometry measurements and the material properties of each component taken in the laboratory, a CAD geometry was developed. Furthermore, the electric and magnetic fields are solved for the geometry configuration and, by implementing a Monte Carlo simulation, the electron trajectories and velocity distributions in the system are calculated. Finally, we use a multi-fluid model to solve a simplified system of a 1 dimensional capacitively coupled plasma and recover the system properties. The method to solve the respective system of equations is the finite element method implemented in the software COMSOL Multiphysics.
Keywords: Método de elementos finitos; Películas delgadas; Método de Monte Carlo; http://purl.org/pe-repo/ocde/ford#1.03.00